Potential of fungi isolated from a mangrove ecosystem in Northern Sulawesi, Indonesia: Protease, cellulase and anti-microbial capabilities - AGUS TRIANTO; OCKY KARNA RADJASA; SUBAGIYO SUBAGIYO; HARTUTI PURNAWENI; MUHAMMAD SYAIFUDIEN BAHRY; RIGNOLDA DJAMALUDIN; AIYEN TJOA; IAN SINGLETON; KAREN DIELE; DARREN EVAN (Society for Indonesian Biodiversity, 2021)
Abstract. Trianto A, Radjasa OK, Subagiyo, Purnaweni H, Bahry MS, Djamaludin R, Tjoa A, Singleton I, Diele K, Evan D. 2021. Potential of fungi isolated from a mangrove ecosystem in Northern Sulawesi, Indonesia: Protease, cellulase and anti-microbial capabilities. Biodiversitas 22: 1717- 1724. The high and relatively unexplored diversity of fungi present in the mangrove ecosystem represents a source of novel biotechnological importance. This study explored the potential of fungi isolated from the mangrove ecosystems to produce proteases and cellulases (commercially important enzymes) and their ability to inhibit pathogenic Vibrio species. Random samples of root, branch, leaf, sediments and litters were collected from 5 different mangrove sites in Manado, North Sulawesi, as a source of fungal isolates. The fungi were isolated on malt extract agar (MEA) and potato dextrose agar (PDA). The isolates were identified mainly based on the molecular methods (18S gene sequence) and examined for their ability to produce proteases, cellulases, and activity against several Vibrio species. Altogether 288 species of fungi were isolated from all samples. The fungi, isolated from leaves showed the highest diversity. A fungal isolate 19 Mba-C2-1 Fusarium equiseti from Avicennia sp. leaf showed the highest protease activity. While, the isolate 19 MT-05-3 Hypocrea sp. from sediment had the highest cellulase activity. From the root of Rhizophora sp., the isolate 19 MT-04-3 identified as Trichoderma viride had the strongest activity against a range of Vibrio species. This work indicates the high potential of fungi isolated from mangrove ecosystems as a source of commercially important enzymes and novel antimicrobial compounds.